Corn Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R.; O'Brien, Daniel M.; Olson, Brian L.S. (My University, 2007)
This publication provides estimated cost and returns for forward farm planning for corn in western Kansas.
MF2150_2007_10
Keywords: MF2150; Crops; Economics; MF